Association between IL1RL1 gene polymorphisms and allergic rhinitis risk in the Chinese Han population. Issue 11 (31st October 2022) - Li, Zhengqing; Ren, Jiajia; Zhang, Jirong; Wang, Xing; Liu, Yonglin; Wang, Qiang
Abstract: Background: Although it has been confirmed that IL1RL1 is involved in the occurrence of allergic rhinitis (AR), the role of IL1RL1 gene single nucleotide polymorphisms (SNPs) in AR is still unclear. Methods: We performed a case–control study including 1000 AR patients and 1000 healthy controls. The four SNPs rs72823628 G > A, rs950881 G > T, rs72823641 T > A and rs3771175 T > A in IL1RL1 were chosen and genotyped using Agena MassARRAY platform. The relationship between IL1RL1 SNPs and AR risk was analyzed by logistic regression and assessed with odds ratios (ORs) and corresponding 95% confidence intervals (95% CIs). Results: Overall analysis revealed that IL1RL1 gene rs72823628, rs950881 and rs3771175 were associated with a reduced AR risk. Stratified analysis showed that the three SNPs (rs72823628, rs950881 and rs3771175) were obviously linked to a reduced risk of AR in males. Moreover, no correlation was observed between haplotypes and reduced AR risk after the false discovery rate (FDR) correction. The false positive report probability (FPRP) analysis was used to further validate significant findings. Conclusion: Our study is the first to indicate that IL1RL1 gene polymorphisms (rs72823628, rs950881 and rs3771175) may be correlated with decreased risk of AR in the Chinese Han population. Abstract : A case–control design was used to study the relationship between L1RL1 gene polymorphisms and allergic rhinitis (AR) risk. The study is the first to indicate that IL1RL1 gene polymorphisms (rs72823628, rs950881 and rs3771175) are correlated with decreased risk of AR in the Chinese Han population.